Politics and the press in Thailand : media machinations - McCargo, Duncan (London ; New York : Routledge, 2000)
This is the first book in English to examine the tangled web of relationships linking newspaper owners, editors and reporters, with leading politicians and power-holders.
Book Cover; Title; Copyright; Contents; Acknowledgements; 1 Introduction; 2 Political news-gathering in Thai language newspapers; 3 The role of political reporters; 4 Inside a political daily; 5 Investigative reporting?; 6 The power of the political columnist; 7 Conclusion; Appendix; Notes; Select bibliography; Index.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Press and politics -- Thailand; LANGUAGE ARTS & DISCIPLINES -- Journalism; Press and politics; Thailand; Massenmedien; Politik; Thailand; Perswezen; Journalistiek; Politieke invloed; Presse et politique -- Thaïlande.